The Effectiveness of Islamic Microfinance Distribution on Microbusiness Owner’s Poverty Alleviation (Case Study: BMT Bina Masyarakat Purworejo) - AGENG PRASETYO; JAENAL EFFENDI; TITA NURSYAMSIAH (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2018)
The objective of the study is to analyze the effectiveness of Islamic microfinance distri- bution and its impact on microbusiness owners’ poverty alleviation in Purworejo. This study used descriptive analysis method that is Likert scale and ordinary least square method (OLS) to analyze the influence of Islamic Microfinance Institution’s financing to microbusiness performance. The impact on the poverty alleviation is indicated by the change of microbusiness owners’ income. The results indicate that Islamic micro-financing is con- sidered to be effective in several aspects, they are proposal aspect, disbursement aspect, utilization aspect, and pay-back aspect of financing. In addition, Islamic microfinance has a positive impact on microbusiness performance and poverty alleviation.